The Value of Combined Large Format Histopathology Technique to Assess the Surgically Removed Breast Tissue following Neoadjuvant Chemotherapy: A Single Institution Study of 40 Cases. (18th October 2012) - Ibarra, Julio A.
Abstract : Historically, neoadjuvant chemotherapy has been used to treat patients with advanced breast disease in an attempt to convert them into candidates for breast conservation surgery. The ultimate goal of histopathologic examination of the specimens removed after neoadjuvant chemotherapy is the identification of either residual disease or positive identification of the tumor bed. We report a series of 40 patients treated with neoadjuvant chemotherapy and evaluation of the surgical specimens by a combination of standard histopathology and the use of large format histopathology techniques.